Nonlinear Creep Model and Parameter Determination of Asphalt. Issue 1 (1st January 2022) - Fan, Xiyan; Jiang, Wenling; Mei, Ning; Su, Chuanqi
Abstract: Asphalt is a kind of typical viscoelastic material. Adding different materials in asphalt composite materials is an important way in road engineering materials. The creep experiments under different stress of asphalt, we used the multivariate model to fit the experimental data to get Burgers model and the creep law of asphalt correlation is best. The Burgers model be expanded by Taylor series, the polynomial creep model of creep compliance and relaxation characterized the coefficient of asphalt specimen can be obtained. Compared to other models, the creep law of asphalts well characterized by polynomial model, multivariate model has a wider range of adaptability compared to polynomial model, and polynomial model of mathematical calculation more simple than multivariate model.